MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPSq) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Mita Afrilia (Jurnal Edukasi dan Penelitian Matematika, 2020)
Various of studies indicate that mathematics learning achievement of Indonesian students is classified as low. The main factors causing this issue are passive teaching-learning process that related to the low  understanding of student’s mathematical concept.  The purpose of this article is written to examine the influence of learning model type think pair square on activeness and understanding of student’s mathematical concept. The methods of data collection used in this article are to search and review the relevant journals after that process the data. The result of this study is indicate that student’s understanding of mathematical concepts increase also students learning process become more active by using a learning model type think pair square.  Keywords __ NHT, Cooperative Learning, Understanding Of Mathematical Consepts